Remoção de matéria orgânica e nitrogênio em filtros biológicos percoladores aplicados ao pós-tratamento de efluentes de reatores UASB - Paulo Gustavo Sertorio de Almeida (2012)
This work aimed to investigate the organic matter (OM) and nitrogen (N) removal in trickling filters post-UASB reactor (UASB/TF system) treating domestic wastewater. The experimental apparatus was comprised by a UASB reactor (16,8 m3) followed by two TFs (height: 1,85-1,90 m) in parallel. The natural ventilated biotowers (TFs) were filled with a vertical plastic media (Rotopack) and a sponge-based packing media (Rotosponge), respectively. The main difference between the two packing media was the presence of polyurethane sponge sheets for Rotosponge. For the operational conditions tested (10 m3.m-2.d-1; 0.30-0.60 kgDQO.m-3.d-1), the use of a sponge-based packing media reduced the probability of failure of the UASB/TF system (COD and TSS: from 20% to 1%; NH4+-N: from 50% to 3%). Because the presence of macrofauna (predators) within TF-Rotopack, the increase of nitrification rates and NH4+-N removals were not observed at low organic loadings (around 0.35 kgCOD.m-3.d-1). For TF-Rotosponge, the nitrification rates was compatible with NOx-N production, considering N-losses. The low intensity of AOB-DGGE bands at lower portions of the TF-Rotosponge reinforced the related reactional volume was not relevant for nitrification at lower organic loadings. N-removal was improved with sponge-based packing media, but still unstable. Because the low biodegradability of UASB effluent and high COD/N (0,25), recirculation (1:1) was not a good strategy for improvements in N-removal. Despite higher OLR led to greater N-removal, heterotrophic denitrification probably was not the only relevant process for N-removal. In terms of OM removal, we observed the operation of UASB/TF without secondary settlers was feasible, in which anaerobic sludge control is a key factor. The retention and consumption of solids within the sponges contributed to such operational simplification. In addition, because the potential for solids retention, we observed the sponge-based packing media improved the robustness of the UASB/TF in a hydraulic shock load event. The current stage of the research shows that a sponge-based packing media is important for enhancements in terms of effluent quality and operational simplification of UASB/TF systems. Furthermore, the new configuration of sponge-based packing media called Rotosponge can enhance the feasibility of scale-up UASB/TF treatment, including when retrofitting is necessary. In addition, to investigate and quantify relevant features related with OM and N removal in the TFs we develop a multispecies, multicomponent models. A detailed analysis using the mechanistic models will provide relevant information regarding the factors responsible for difference in performance between the TFs post-UASB reactors.